Penerapan Metode Pomodoro Dan Cornell Notes Guna Meningkatkan Kualitas Belajar Siswa di MI Al-Marhamah - Bastomi, Mohamad; Aisya, Adinda Alifia; Nisa’i, Chayrun; Suhartatik, Diah Putri; Rahmawati, Iis; Fauziah, Nanik; Hidayah, Nikmatul; Amalya, Rifky; Salim, Vincencia Carolina (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
MI-Almarhamah students tend not to be able to take part in learning activities well. The majority of them are hyperactive students and cannot focus during long activities. This causes the class atmosphere to be not conducive and student learning outcomes are low. This service aims to improve the quality of student learning at MI-Almarhamah. The methods used are socialization, training and direct mentoring in class as well as monitoring and evaluation related to the application of the Pomodoro and Cornell Notes methods. This community service is able to improve the quality of student learning, make the classroom atmosphere more conducive and help teachers apply appropriate methods for students.